Investigation of DGS CDRA for high gain applications - Zakariya, M.A. (Springer Verlag, 2017)
A single element rectangular aperture coupled cylindrical dielectric resonator antenna (CDRA) with a plane reflector is proposed. A plane reflector is integrated at the back of the proposed CDRA to provide unidirectional radiation pattern with the improvement in gain and sidelobe level. The gain of the DRA is improved by reducing the back radiation caused by the aperture coupling. The peak gain of the antenna has been enhanced about 4.3 dB from 4.7 to 9.0 dBi at 5.18 GHz. The measured impedance bandwidth achieved for the proposed DRA is 0.2 GHz for S11 < −10 dB from 5.17 to 5.37 GHz. The radiation pattern with broadside radiation and low back radiation has been obtained. The experimental and measured results show that the antenna is high gain, small in size and satisfies the basic requirements of WLAN 802.11a. © Springer Science+Business Media Singapore 2017.